Studies on the biology of the brown hare (Lepus europaeus) with particular reference to behaviour - Holley, Anthony J. F. (Durham University, 1992)
Behaviour of the brown hare (Lepus europaeus) was studied on the Somerset levels, U.K., between 1977 and 1987. The hare is exclusively nocturnal when nights are longest and part-diurnal when they are shortest but the transition is not smooth. There is a linear dominance hierarchy between bucks. The nearer a doe is to oestrus, the higher the rank of her escort. Some pre-partum does monitor the prospective birthsite. They are only occasionally escorted by bucks. In contrast, a non-monitoring pregnant doe was regularly escorted. Does lie up within 250m of their litters but take a more circuitous route when visiting them and 'detour when foxes are encountered. Four Autumn litters were suckled for between six and nine weeks. Sucking leverets usually sniff-noses when meeting up, followed by a short period of locomotor play after which they go quietly to the nursing point. Some weaned leverets continued to meet up. The principal component of locomotor play is 'streaking' - running top speed back and forth down a familiar route. Leverets disperse after nursing to a daily increasing extent. Leveret distress screams were audible from a distance of 550m. As a visible signal, the buck's white tail flag seems to serve no purpose. The doe uses her tail flag to lead her litter. Only does shake their tails which they do exclusively in the near presence of bucks; the bucks then sniff the ground underneath. Hares were not observed to signal to each other by body postures or to use their ears for purposes other than acoustic. Does convey a threat to bucks by flattening their ears and lifting their muzzles. Adults, particularly bucks; sniff a partner's nose for olfactory information as an alternative when the ano-genital region is inaccessible, but are frequently threatened when so doing. All chin-marking was by bucks of which 80% were solitary. Hares approached in the open by foxes stand bipedal when, on average, the fox is about 30m distant. The relevance of the behaviour patterns are discussed.